Hybridity : limits, transformations, prospects - Prabhu, Anjali (Albany : State University of New York Press, 2007)
Annotation This critical engagement with some of the most prominent contemporary theorists of postcolonial studies reevaluates recent theories of hybridity and agency. Challenging the claim that hybridity provides a site of resistance to hegemonic and homogenizing forces in an increasingly globalized world, Anjali Prabhu pursues the ways in which hybridity plays out in the Creole, postcolonial societies of Mauritius and La Reunion, two small islands in the Indian Ocean, and offers an introduction to the literature and culture of this lesser-known region of Francophonie. She also reconsiders two major theorists from the Francophone context, Edouard Glissant and Frantz Fanon, through a provocatively Marxian framing that reveals these two writers shared more in common about agency and society than has previously been recognized. Book jacket.
Hybridity in contemporary postcolonial theory : examining agency -- Hybridity in La Réunion : Monique Boyer's Métisse and the nation as necessity -- Theorizing hybridity : colonial and postcolonial La Réunion -- On the difficulty of articulating hybridity : africanness Mauritius nation -- Ethnicity and the fate of the nation : reading Mauritius -- Interrogating hybridity : subaltern agency and totality in postcolonial theory through Edouard Glissant's Poétique de la relation -- Frantz Fanon and hybridity : a closer look at narrative in Black skin, white masks -- Afterword : why hybridity now?
Includes bibliographical references (pages 165-174) and index.
Print version record.
Keywords: Reunionese literature (French) -- History and criticism; Réunion -- Civilization; Mauritius -- Civilization; Racially mixed people in literature; Racially mixed people -- Psychology; Miscegenation; LITERARY CRITICISM -- European -- French; Civilization; Miscegenation; Racially mixed people in literature; Racially mixed people -- Psychology; Reunionese literature (French); Mauritius; Réunion.; Electronic books; Electronic books; Criticism, interpretation, etc